The Role of Theology in Religious Education - Boys, Mary C. (Horizons, 1984)
The intensified efforts in recent years to bring definitional clarity to the field of religious education involve not simply elucidating the role of theology but also exploring the function of religious studies. A proposal is made in this essay that both theology and religious studies make different and necessary contributions to religious education, though neither subsumes it. The context for this argument is established by means of an initial review of the literature of religious education regarding the varied perspectives on the role of theology and then by attention to the relationship of theology and religious studies. The concluding section consists of three propositions specifying a conceptualization of the field of religious education with distinct functions for theology and religious studies.